The laboratory, a transit for the theoretical-practical knowledge in the Biodiesel Synthesis - Garcia Gonzalez, Conrado; Arcos Vega, José Luis (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This experimental methodologically designed research is of qualitative nature and information was obtained based on the observation method of 15 students from each group, as an extracurricular didactical proposal, conducted within the General Chemistry subject that is part of the Core Studies in the Engineering program. It was implemented for three consecutive semesters: 2018-1,2 and 2019-1, in the Chemistry Lab of the Universidad Autónoma de Baja California, Guadalupe Victoria Campus in the Mexicali Valley, in Baja California, Mexico. The General Chemistry subject is a compulsory course and is taught in the second semester of the core studies in the Engineering Sciences program.